Monitoring changes in performance, physiology, biochemistry, and psychology during overreaching and recovery in triathletes - Coutts, A. J.; Wallace, L. K.; Slattery, K. M. (International Journal of Sports Medicine, 2007)
The present investigation compared responses in previously identified physiological, biochemical, and psychological markers of overreaching in triathletes. Sixteen experienced male triathletes (V·O2max [mean ± SD] = 55.7 ± 4.9 mL · kg-1 · min-1, age = 31.3 ± 11.7 yr) were divided into matched groups according to physical and performance characteristics, and were randomly assigned to either intensified training (IT) or normal training (NT) groups. Physiological, biochemical, and psychological measures were taken at baseline, following four weeks of overload training and following a two-week taper. The IT group completed 290 % greater physical training load than the NT group during the overload period. The subjects completed a 3-km run time trial (3-km RTT) each week in order to assess the time course of change in endurance performance. 3-km RTT performance was significantly reduced (3.7 ± 7.5 %; p < 0.05) following four weeks of overload training in the IT group confirming a state of overreaching. During the same period, 3-km RTT performance significantly improved in the NT group (3.0 ± 1.1 %; p < 0.05). Following the two-week taper, 3-km RTT performance significantly improved in the IT group (7.0 ± 5.6 %; p < 0.05). Hemoglobin concentration significantly decreased and urea increased in both groups during the overload period (p < 0.05). During the taper hemoglobin normalized with a greater increase in the IT group compared to the NT group (p < 0.05). A significant increase in free testosterone to cortisol ratio was also observed in the IT group compared to the NT group during the taper (p < 0.05). No significant changes were observed for any other biochemical variables during the period of investigation. The RESTQ-76 Sport questionnaire showed an impaired recovery-stress state with increased training load, which improved following the taper in the IT group (p < 0.05). These present results suggest that none of the physiological and biochemical variables measured in this study were effective for the early identification of overreaching in experienced triathletes. However, the RESTQ-76 Sport questionnaire may provide a practical tool for recognizing overreaching in its early stages. These findings have implications for monitoring training status in athletes in a practical training setting.